UPAYA PENINGKATAN KUALITAS TANAMAN KEDELAI (Glycine max L. Merill) MELALUI PEMANFAATAN BIOTEKNOLOGI DALAM MENGATASI KELANGKAAN PANGAN - Edi Tando; Muh Afif Juradi (Percetakan Umi Toaha Makassar, 2019)
Population growth the rapidly is currently a major challenges to business world food supply. The development of biotechnology begins with technology genetically engineered has accelerated. Products of biotechnology plants resembling plants provenance, but having the characteristics of certain that causes those plants better. Plant products of biotechnology which has been approved for food as having the nature of : 1) resistance to pests and disease , 2) resistance to herbicide, 3) nutrition changes and 4) content increased save resources. The purpose of drafting this paper is to provide information about improving the quality of the soybean plant ( Glycine max l .Merill ) through the use of biotechnology in addressing scarcity of food.The genetically engineered in plants soybean , includes extraction process dna ( modification ctab ) method of the leaves of plants tangential and soybean R1 R2. Fragments of dna the genome of 0.8 kb involved in tolerant asam-al at b . Japonicum 38 has successfully isolated using inverse PCR technique, Fragments of dna has been successfully diklon into plasmid vector pgemt-easy ( 3kb ) produce recombinant plasmid pgemt-38 a 3.8 family planning. Ttransfer genes pinii in plants soy has successfully done through a . Tumefaciens with one of his event at1 ( tidar ) showing the pcr positive on pinii genes. Protocol best for soybean through the transformation of a . Tumefaciens is using eksplan cotyledon young with the density of bacteria 1 x 108 / cell mls inoculation / long 90 minutes and long kokultivasi 5 days. The soybean plant AT1R1 ( tidar ) transformation through a result. Tumefaciens a little more resistant to pest borer rather than the pods the soybean plant nontransgenik (control)